Flourishing tumor organoids: History, emerging technology, and application - Qian Yang; Mengmeng Li; Xinming Yang; Zian Xiao; Xinying Tong; Ayinuer Tuerdi; Shisheng Li; Lanjie Lei (Wiley, 2023)
Abstract Malignant tumors are one of the leading causes of death which impose an increasingly heavy burden on all countries. Therefore, the establishment of research models that closely resemble original tumor characteristics is crucial to further understanding the mechanisms of malignant tumor development, developing safer and more effective drugs, and formulating personalized treatment plans. Recently, organoids have been widely used in tumor research owing to their advantages including preserving the structure, heterogeneity, and cellular functions of the original tumor, together with the ease of manipulation. This review describes the history and characteristics of tumor organoids and the synergistic combination of three‐dimensional (3D) culture approaches for tumor organoids with emerging technologies, including tissue‐engineered cell scaffolds, microfluidic devices, 3D bioprinting, rotating wall vessels, and clustered regularly interspaced short palindromic repeats‐CRISPR‐associated protein 9 (CRISPR‐Cas9). Additionally, the progress in research and the applications in basic and clinical research of tumor organoid models are summarized. This includes studies of the mechanism of tumor development, drug development and screening, precision medicine, immunotherapy, and simulation of the tumor microenvironment. Finally, the existing shortcomings of tumor organoids and possible future directions are discussed.